Is Monetary Policy Effective When Credit is Low? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Monetary policy, at least in part, operates through both an interest rate and credit channel. The question arises, therefore, whether monetary policy is a less potent a device in affecting output and inflation in countries that have low levels of credit and where investment and consumption are not financed by borrowing in local currency. This paper employs a Panel Vector Auto Regression approach to examine the empirical evidence in a broad sample of emerging market countries. The data suggests that the effectiveness of changes in policy interest rates in influencing the path of inflation appear to be unrelated to the level of credit and that, instead, the willingness to allow exchange rate flexibility is a far more important determining factor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet